Reconsidering “Law” in the Letter of James - Du Toit, Philip la Grange (Neotestamentica, 2020)
Amidst various interpretative options about the identities of the author and addressees of the Letter of James, one’s interpretation of the letter’s discourse on the concept of law plays a critical role in the way in which these identities are reconstructed. Two laws or principles form part of the discourse in the Letter of James, namely, the Mosaic law (esp. 2:9-11) and the kingdom-principle of freedom (esp. 1:25; 2:8, 12). It is argued that the kingdom-principle of freedom in Christ is presented to the recipients in contrast with a probable tendency among these Judaean Christ-believers to be torah-orientated, especially involving the judging of people on the basis of the Mosaic law. In this scenario, the author can be identified as James, the half-brother of Christ, who is not fully torah abiding. It is argued that James uses a rhetorical strategy of frankness in terms of the issues in the congregation he addresses together with a strategy of subtlety in respect of his discourse on law. In his rhetorical strategy on law he contextualises his message in such a manner that he identifies with the recipients’ frame of reference of law. By doing so, he attempts to lead them to a different perception on law and present to them a different principle by which they can become whole in their personal and corporative life.